Financial Sector Assessment Program Update : Philippines - The Insurance Sector, A Market and Risk Based Review - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
This note summarizes the conclusions of the review of the insurance sector in the Philippines as part of the Financial Sector Assessment Program (FSAP). The main objectives of the assessment are to review the performance and structure of the insurance sector in the Philippines with respect to: a) the potential exposure of the sector to vulnerabilities, either generated from the sector or in response to other circumstances outside the sector that could either be magnified or dampened by the sector; b) the potential for the sector to grow and develop, in its own context and also to contribute to the overall long term growth and development of the economy and the well-being of the Philippines people; and c) the relationship between the oversight and regulatory arrangements for the sector against international norms and best practices. In summary, the key conclusions of this analysis are: i) the financial performance of the sector has been particularly stable although the outlook is less sanguine; ii) financial vulnerabilities are present but the challenges would appear to be manageable with careful and vigilant oversight and some targeted policy measures; and iii) opportunities for growth in the sector are wide ranging.